High Dose Intravenous Vitamin C for Preventing The Disease Aggravation of Moderate COVID-19 Pneumonia. A Retrospective Propensity Matched Before-After Study - Zhao, Bing; Liu, Min; Liu, Ping; Peng, Yibing; Huang, Jun; Li, Mengjiao; Wang, Yihui; Xu, LiLi; Sun, Silei; Qi, Xing; Ling, Yun; Li, Jian; et al. (Frontiers in Pharmacology, 2021)
Abstract Background Coronavirus disease 2019 (COVID-19) pandemic is continuing to impact multiple countries worldwide and effective treatment options are still being developed. In this study, we investigate the potential of high-dose intravenous vitamin C (HDIVC) in the prevention of moderate f COVID-19 disease aggravation. Methods In this retrospective before-after case-matched clinical study, we compare the outcome and clinical courses of patients with moderate COVID-19 patients who were treated with an HDIVC protocol (intravenous injection of vitamin C, 100 mg/kg/day, 1 g/hour, for 7 days from admission) during a one-month period (between March 18 and April 18, 2020, HDIVC group) with a control group treated without the HDIVC protocol during the preceding two months (January 18 to March 18, 2020). Patients in the two groups were matched in a 1:1 ratio according to age and gender. Results The HDIVC and control groups each comprised 55 patients. For the primary outcomes, there was a significant difference in the number of patients that evolved from moderate to severe type between the two groups (HDIVC: 4/55 vs. control: 12/55, relative risk [RR] = 0.28 [0.08, 0.93], P = 0.03). Compared to the control group, there was a shorter duration of systemic inflammatory response syndrome (SIRS) (P = 0.0004) during the first week and lower SIRS occurrence (2/21 vs 10/22, P = 0.0086) on Day 7 (6-7 days after admission). In addition, HDIVC group had lower C-reactive protein levels (P = 0.005) and higher number of CD4+ T cells from Day 0 (on admission) to Day 7 (P = 0.04).” The levels of coagulation indicators, including activated partial thromboplastin time and D-dimer were also improved in the HDIVC compared to the control group on Day 7. Conclusion HDIVC may be beneficial in limiting disease aggravation in the early stage of COVID-19 pneumonia, which may be related to its improvements on the inflammatory response, immune function and coagulation function. Further randomized controlled trials are required to augment these findings.